Shear stress regulates inflammatory and thrombogenic gene transcripts in cultured human endothelial progenitor cells - Lund, Trine; Hermansen, Stig E.; Andreasen, Thomas V.; Olsen, Jan Ole; Østerud, Bjarne; Myrmel, Truls; Ytrehus, Kirsti (Thrombosis and Haemostasis, 2010)
Shear stress has an established effect on mature endothelial cells, but less is known about how shear stress regulates endothelial progenitor cells (EPCs). In vitro expanded EPCs isolated from adult human blood represent a novel tool in regenerative vessel therapy. However, in vitro culturing may generate cells with unfavourable properties. The aim of the present study was therefore to assess whether shear stress may influence the inflammatory and thrombotic phenotype of in vitro expanded EPCs. In late outgrowth EPCs, 6 hours of shear stress (6.0 dynes/ cm2) significantly reduced the mRNA levels of IL-8, COX2, and tissue factor (TF) compared to static controls. This was associated with a reduced TF activity. In contrast, mRNA expression of NOS3 was significantly increased following 6 and 24 hours of shear stress. In accordance with this, NOS3 protein expression was increased following 24 hours of shear stress. Overall stimulation with the proinflammatory mediator, TNFα, for the final 2 hours increased the mRNA expression of IL-6, IL-8, MCP-1, ICAM1, and TF. However exposure to 6 hours of shear stress significantly suppressed the inductory potential of TNFα to increase the mRNA levels of IL-6, IL-8, COX2, and TF. Additionally, TNFα increased TF activity approximately 10 times, an effect that was also significantly reduced by exposure to 6 and 24 hours of shear stress. The effect of shear on the gene levels of TF and NOS3 were not blocked by the NOS inhibitor L-NAME. These observations suggest that EPCs are capable of functionally responding to shear stress.
Keywords: Late outgrowth endothelial progenitor cells; shear stress; inflammation; tissue factor